Multi-professional rehabilitation model among Older Persons after Hip Fracture Surgery: Review - Wantonoro, Wantonoro; Nguyen, Tuan Van; Yang, Hsiu-Ling (Universitas Muhammadiyah Semarang, 2024)
Hip fracture in the elderly is a major health problem. Multi-professional rehabilitation approaches were recommended; however, there were various multi-professional rehabilitation models; therefore, identifying the multi-professional rehabilitation model, especially for older persons after hip fracture surgery, is needed. The aim of this review study is to identify a multi-professional rehabilitation model among the elderly with hip fracture surgery. A literature search for relevant articles in PubMed, Scopus, Embase, and CINAHL was used. Studies that met the following criteria were included: Patients with hip fracture surgery, multi-professional rehabilitation, and randomized controlled trial study, measured physical outcome, published during 2018 to 2024, English full-text article. Finally, six articles met inclusion criteria. The multi-professional rehabilitation model among older persons after hip fracture surgery includes geriatric interdisciplinary home rehabilitation, multicomponent home-based rehabilitation, comprehensive geriatric care, fragility integrated rehabilitation, and comprehensive orthogeriatric care. In addition, hip fracture rehabilitation problems include fear of falling and comorbid and postoperative complications. The multi-professional rehabilitation model improved the quality of life of the older persons after hip fracture surgery. Multi-professionals’ rehabilitation model effectively improved physical performance among older persons after hip fracture surgery. Identifying multi-professional rehabilitation models with specific needs for older persons after hip fracture surgery are recommended in clinical practice.